Biphenylene-containing polycyclic conjugated compounds - Dengiz, Cagatay (Beilstein Journal of Organic Chemistry, 2023)
There has been a growing emphasis on the synthesis of polycyclic conjugated compounds, driven by their distinct structural characteristics that make them valuable candidates for use in cutting-edge technologies. In particular, acenes, a subgroup of polycyclic aromatic compounds, are sought-after synthetic targets due to their remarkable optoelectronic properties which stem from their π-conjugation and planar structure. Despite all these promising characteristics, acenes exhibit significant stability problems when their conjugation enhances. Various approaches have been developed to address this stability concern. Among these strategies, one involves the incorporation of the biphenylene unit into acene frameworks, limiting the electron delocalization through the antiaromatic four-membered ring. This review gives a brief overview of the methods used in the synthesis of biphenylenes and summarizes the recent studies on biphenylene-containing polycyclic conjugated compounds, elucidating their synthesis, and distinct optoelectronic properties.
Keywords: acenes; biphenylene; [N]phenylenes; polycyclic aromatic compounds